Theoretical and experimental studies on the electrodeposited nanocrystalline Ag coatings from a novel Ag2O-based non-cyanide electrolyte - Li, Ruopeng; Jiang, Jie; Li, Yaqiang; Ren, Penghui; Shen, Baicheng; Qin, Jiang; Zhang, Jinqiu; An, Maozhong; Yang, Peixia (Journal of industrial and engineering chemistry (Seoul, Korea), 2024)
Functional silver coatings have been widely applied in fields of electrochemical energy conversion systems,electronics industry and antibacterial materials, and exploiting new non-cyanide silver electroplating bath systemis of great significance for promoting the application. In this work, a new type of cyanide-free electrodepositedsilver (Ag) system was developed with Ag2O as the main salt, 5,5-dimethyl hydantoin (DMH) as thesilver ion complexing agent and potassium carbonate as the conductive salt. Comprehensive quantum chemicalcalculations demonstrate that the new silver-based system has the solvation structure of [Ag(C5H7N2O2)2] (5N(2)-Ag). To further, roles of additives combination (L-cysteine and 2,2-bipyridine) and their fundamentalmechanism on the silver electrodeposition process was further investigated by electrochemical tests and theoreticalcalculations. First-Principles calculation and simulation of molecular dynamics reveal that this additivecouple have coordination interactions with Ag+, while strong adsorption on the Ag (111) surface. SEM and XRDanalyses showed that the combination of L-cysteine and 2,2-bipyridine achieved an ideal silver coating with goodmorphology and a low grain size of 22.1 nm, verifying the great potential of the novel system to prepare highqualitysilver coatings. KCI Citation Count: 0